The Effectivity of Marine Bio-activator and Surimi Liquid Waste Addition of Characteristics Liquid Organic Fertilizer from Sargassum sp. - Putri Wening Ratrinia; Uju Uju; Pipih Suptijah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
AbstractOrganic fertilizer is highly recommended for soil and plant because it can improve the productivity and repair physical, chemical, and biological of soil. Sargassum sp. and surimi liquid wastes contain organic matter and nutrient needed by plants and soils. The addition of marine bio-activator which contains bacterial isolates from litter mangrove serves to accelerate the composting time and increases the activity of microorganisms in the decomposition process. The purpose of this study was to determine optimum time and the best formulation of decomposition process organic fertilizer. Raw materials used a waste of seaweed Sargassum sp., marine bio-activator and surimi liquid waste from catfish (Clarias sp.). The research was conducted six treatments control, Sargassum sp. + marine bio-activator, surimi liquid waste , Sargassum sp. + marine bio-activator + surimi liquid waste 80%, 90%, 100%. All treatments were fermented for 9 days and analysed the C-organic, total N, C/N ratio, P2O5, K2O on days 0, 3, 6 and 9. The results showed the optimum fermentation period was on the 6th day. The most optimum concentration of surimi liquid waste added was at a concentration of 90%, with characteristics of the products was C-organic 0.803±0.0115%, total N 740.063±0.0862 ppm, C/N ratio 10.855±0.1562, P2O5 425.603±0.2329 ppm, K2O 2738.627±0.2836 ppm.